Students’ Habit of Listening to English Songs and Pronunciation Ability in Learning English - Pamelo, Hernita; Lotulung, Christa Vike (SUMIKOLAH: Jurnal Ilmu Pendidikan, 2024)
In learning English, one of the obstacles experienced by students is their pronunciation ability in learning English. Therefore, this study aims to determine the relationship between students’ habits of listening to English songs and their pronunciation abilities in learning English. This research used quantitative methods, and the respondents were 69 students in class 8A, B and F of SMP Negeri 2 Airmadidi. The sampling technique used in this research was convenience and a questionnaire as the instrument. The questionnaire used in this research was adopted from Olah (2018), and originally from Arsyida (2018). The findings of this research descriptively showed that students’ listening habits in English songs (M= 2.7686) were medium criteria, and their pronunciation ability (M=85.43) was a good percentage. The research results also found p-value = 0.072 > 0.05 and the correlation coefficient (r = 0.308) can be concluded that there is no significant correlation between students’ habits of listening to English songs and their pronunciation abilities in learning English.